المذهب الفقهي في المغرب والأندلس بين القرنين (3هـ/6هـ) تواصل أم تنافر ؟ - خضرة, علي (جامعة الوادي - University of Eloued, 2022)
لقد كان للمدارس الفقهية دور كبير في نشر العلم وبعث الحضارة الاسلامية منذ بذورها الأولى في المغرب والأندلس ، ومن منطلق كوننا جزائريين فإننا مطالبون بدراسة تاريخ المذاهب الفقهية التي انتشرت ببلاد المغرب وما علاقتها ببلاد الاندلس ، والدور الذي لعبته هذه المنطقة في نشر الاسلام في إفريقيا بالأخص ، وفي العالم أجمع . ومن هنا نطرح التساؤلات التاليةّ: ما هي أهم المذاهب الفقهية المعروفة في المغرب والأندلس خلال الفترة الممتدة من بداية القرن الثالث الهجري إلى نهاية القرن السادس ؟. وماهي الآثار السلبية والايجابية التي خلفتها المذاهب الفقهية بين الأتباع ؟، ولا يزال بعضها إلى يومنا هذا . Summary: The schools of jurisprudence have played a major role in spreading knowledge and resurrecting Islamic civilization since its first seeds in Morocco and Andalusia. On the basis of our being Algerians, we are required to study the history of the jurisprudential schools that spread in the Maghreb, and what is their relationship to Andalusia, and the role that this region played in spreading Islam in Africa in particular and in the world at large. Hence, we ask the following questions: What are the most important schools of jurisprudence known in Morocco and Andalusia during the period extending from the beginning of the third century AH to the end of the sixth century? And what are the negative and positive effects left by the jurisprudence schools among the followers, and some of them are still to this day Doctrines of Morocco Andalusia
The jurisprudential doctrine in Morocco and Andalusia between the two centuries (3 AH / 6 AH) continuity or dissonance.?
مقال
Keywords: المذاهب الفقهية، المغرب، الأندلس; Doctrines ,Maghreb, Andalusia